Chains of extraction: shifting bioeconomies in India and East Africa - Gondouin, Johanna; Eriksson, Åsa; Thapar-Björkert, Suruchi (Frontiers in Sociology, 2024)
Since the early 2000s, India has been a world leading hub for cross border reproductive treatments, in particular surrogacy, with the nation positioning itself as the “mother destination” for transnational commercial surrogacy, offering “First world services at Third world prices”. State policies, lack of legal regulation, state of the art medical infrastructure and a steady supply of women ready to take on the role as surrogate mothers against meager remuneration have been key factors behind the Indian success story. Yet, a gradual process of regulation in recent years, culminating in the introduction of the Surrogacy (Regulation) Bill 2020, has forced the industry to reinvent itself in order to maintain its role as a market leader in a booming global bioeconomy. This article takes the 2020 bill as a starting point for an exploration of the key trajectories that the Indian reproductive industry has taken since. This includes moving into new market segments, such as the unregulated practice of oocyte donation, and expanding globally into new geo-political contexts. Through these practices, India has successfully rebranded itself as a world leading “pre-conception assemblage hub” where embryos are assembled and implanted into surrogates who carry their pregnancies to term in countries with no protective legislation. The article begins to map the emerging links between the reproductive industry in India and East Africa - where diasporic networks are mobilized in the creation of new reproductive markets, dominated by Indian IVF providers. In particular, we discuss the current expansion in Kenya, which we situate against the backdrop of the colonial entanglements between the two countries. While the ART industry in Kenya is still young, we suggest that these emerging developments illuminate the effect of the ban on commercial surrogacy in India, which appears to have resulted in a partial relocation to countries that lack regulation, shifting the precarious conditions of surrogates in India to other women, elsewhere, in ways that rearticulate colonial racial hierarchies and migration patterns.